The Legal Concept of Limited Liability Company Based on Social-Justice Through Corporate Social Responsibility - Is, Muhamad Sadi; Saputra, Jemmi Angga (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2021)
The presence of Law Number 40 of 2007 concerning Limited Liability Companies is expected to ensure the welfare of the community around the company through the Corporate Social Responsibility program. This study uses a qualitative research method with a literature approach and legislation approach. The results of the study state that in reality, there are still many limited companies that do not implement Corporate Social Responsibility programs because there are no firm sanctions, both criminal, civil and administrative sanctions against limited companies that do not implement the Corporate Social Responsibility program so that social justice for the surrounding community limited liability company is not reached.Keywords: Limited Liability Company; Social Justice; Corporate Social Responsibility Konsep Hukum Perseroan Terbatas Berbasis Keadilan Sosial Melalui Tanggung Jawab Sosial Perusahaan AbstrakHadirnya Undang-Undang Nomor 40 Tahun 2007 tentang Perseroan Terbatas diharapkan dapat menjamin kesejahteraan masyarakat di sekitar perusahaan melalui program Coporate Social Responsibility. Penelitian ini menggunakan metode penelitian Kualitatif dengan pendekatan literatur dan pendekatan peraturan perundang-undangan. Hasil penelitian menyatakan bahwa dalam realitanya, masih banyak perseroan terbatas yang tidak melaksanakan program Corporate Social Responsibility karena disebabkan belum adanya sanksi yang tegas baik sanksi pidana, perdata dan sanksi administrasi terhadap perseroan terbatas yang tidak melaksanakan program Coporate Social Responsibility sehingga keadilan sosial bagi masyarakat di sekitar perseroan terbatas tidak tercapai.Kata Kunci: Perseroan Terbatas; Keadilan Sosial; CSR Правовая концепция общества с ограниченной ответственностью, основанного на социальной справедливости через корпоративную социальную ответственность АннотацияОжидается, что наличие Закона № 40 от 2007 года об обществах с ограниченной ответственностью обеспечит благополучие общества вокруг компании посредством программы корпоративной социальной ответственности. В этом исследовании используется качественный метод исследования с использованием литературного подхода и законодательного подхода. Результаты исследования показывают, что на самом деле существует множество компаний с ограниченной ответственностью, которые не реализуют программы корпоративной социальной ответственности, поскольку отсутствуют жесткие санкции, как уголовные, так и гражданские и административные, в отношении компаний с ограниченной ответственностью, которые не реализуют программу корпоративной социальной ответственности, так что социальная справедливость для общества вокруг общества с ограниченной ответственностью не достигается.Ключевые Слова: Общество С Ограниченной Ответственностью; Социальная Справедливость; Корпоративная Социальная Ответственность